Learning Intensity Effects in Students Mental and Physical Health - Evidence from a Large Scale Natural Experiment in Germany - Sarah Hofmann; Andrea Muehlenweg (University of Duisburg-Essen, CINCH - Health Economics Research Center, 2017)
In this study, we analyze health effects of a recent education reform in Germany exposing students to increased schooling intensity. The reform shortened the higher secondary education track by one year. As the overall curriculum required for graduation was held constant, this led to an increase in instruction hours in the remaining school years. The reform has been introduced at different points in time across federal states, providing us with a difference-in-difference setup for analysis. Based on data from the German SocioEconomic Panel Study (SOEP), our results imply that the reform significantly reduced adolescents self-rated mental health status. The overall effect on the mental component summary score (MCS) is about a quarter of a standard deviation. Examining MCS subdimensions, we find detrimental effects of the reform on vitality and on emotional balance. We also observe significant impacts on self-assessed general physical health.
Keywords: J24; I14; I26; 330; Adolescent health; schooling intensity; school reform; natural experiment